Osmotic concentration of urine in the dynamics of the development of alloxan-induced experimental diabetes - Olenovych, Olha; Zukow, Walery (Journal of Education, Health and Sport, 2022)
In order to clarify the peculiarities of the osmotic concentration of urine in the dynamics of the development of alloxan-induced experimental diabetes mellitus (DDM), studies were conducted on 54 sexually mature non-linear male white rats, in which DDM was simulated by a single intraperitoneal injection of alloxan solution (Alloxan monohydrate, "Acros Organics", Belgium) at a dose of 160 mg/kg of body weight after a previous 12-hour food deprivation with preserved access to water. 10, 25, and 45 days after the introduction of the diabetogenic substance, 24 alloxan-diabetic rats, as well as 30 control (intact) animals, were loading with tap water in a volume of 5% of body weight, urine was collected for 2 hours, euthanasia was performed by decapitation under light ether anesthesia. In blood samples, the level of glucose and creatinine was determined, in urine samples, after evaluating the water-induced 2-hour diuresis (in ml/100 g of body weight in 2 hours), the concentration of creatinine was determined, the clearance of endogenous creatinine, the clearance of osmotically free water, as well as relative (tubular) reabsorption of water, determined the content of glucose, urea, its excretion, including per 100 μl of glomerular filtrate, as well as urine osmolarity. The results of the study allow us to state that as the duration of experimental diabetes is prolonged, the pathogenetic significance of hyperfiltration, which determines the speed of fluid movement along the tubule and the intensity of its absorption, weakens in relation to the processes of osmotic concentration of urine, yielding to other factors, such as the osmolarity of the medulla of the kidneys, as well as the presence of substances in the liquid of the distal segment and collecting tubes, the reabsorption of which can change their concentration in the collecting tubes as the urine progresses. In diabetes, in addition to glucose, such substances include urea. Attempts to analyze the renal excretion of urea revealed that changes in its urinary concentration are definitely correlated with the dynamics of changes in urine osmolality. Moreover, it can be assumed that urea transport disorders in the diabetic kidney occur earlier than the ability to excrete osmotically active substances in general. A joint study of the processes of renal transport of urea and urine osmolarity can serve as an early verifier of tubulointerstitial damage. Nevertheless, to increase the reliability of the interpretation of the features of the osmotic concentration of urine in diabetes, we consider it necessary to study the nature of the renal transport of electrolytes (sodium, potassium, calcium, and ammonium).